Evaluation of the Anti-Inflammatory and Antinociceptive Effects of the Essential Oil from Leaves of Xylopia laevigata in Experimental Models. (3rd July 2014) - Queiroz, João Carlos C.; Antoniolli, Ângelo R.; Quintans-Júnior, Lucindo J.; Brito, Renan G.; Barreto, Rosana S. S.; Costa, Emmanoel V.; da Silva, Thanany B.; Prata, Ana Paula Nascimento; de Lucca, Waldecy; Almeida, Jackson R. G. S.; Lima, Julianeli T.; Quintans, Jullyana S. S.
Abstract : Xylopia laevigata (Annonaceae) is a medicinal plant used in folk medicine to treat pain and inflammation. Thus, we investigated the possible antioxidant, antinociceptive, and anti-inflammatory effects of X. laevigata leaf essential oil (EOX) in animal models. Our EOX sample showed the presence of γ -muurolene (17.78%), δ -cadinene (12.23%), bicyclogermacrene (7.77%), and α -copaene (7.17%) as main compounds. EOX presented a strong antioxidant potential according to the DPPH, TBARS, and nitrite production tests. Additionally, pretreatment with EOX, in mice, also significantly produced (P < 0.05 or P < 0.001 ) antinociceptive effect by reduction of nociceptive behavior (in formalin and writhing tests). The EOX showed c-Fos label in the olfactory bulb, piriform cortex, and periaqueductal gray. Acute administration of EOX exhibited a significant (P < 0.01 or P < 0.001 ) anti-inflammatory profile in the carrageenan-induced peritonitis and by the carrageenan-induced hindpaw edema tests in mice. Our results provide evidence for the use of X. laevigata by traditional medicine practitioners in the management of pain and inflammatory disorders.